Study of SCA-Induced Rock Crack Propagation under Different Stress Conditions Using a Modified Cohesive Element Method - Shen Wang; Hani Mitri; Huamin Li; Dongyin Li; Wen Wang (Advances in Civil Engineering)
When inducing cracks, soundless cracking agents (SCAs) do not generate vibration, harmful gas, dust, nor flying rock fragment, making them suitable for hard rock roof breaking, rock burst prevention, oil or gas reservoir stimulation, and building demolition. In this study, SCA-induced crack initiation and propagation in different stress conditions were modelled using a modified cohesive element method. A new traction-separation law for describing rock compressive shear strength was proposed. The crack length and direction in bidirectional isobaric and unequal stress fields were analyzed in detail. The crack initiation pressure and the incremental ratio of crack length to SCA expansion pressure were proposed as two indicators to evaluate the difficulty in rock breaking in deep underground. Results indicate that (1) the modified cohesive element method used in this study is feasible to model crack propagation in deep rocks; (2) the maximum expansion pressure of SCAs depends on rock elastic modulus and geostress field and should be measured under a condition similar to deep underground prior to SCA borehole spacing design; when using the SCAs with a maximum expansion pressure of 100 MPa in 600 m underground, the suggested borehole spacing is less than 220 mm; and (3) σ3 dominates the crack initiation pressure while the principal stress ratio σ3/σ1 and notch direction control the direction of crack propagation.